Military brass vs. civilian academics at the National War College a clash of cultures - Wiarda, Howard J. 1939- (Lexington Books, 2011)
The National War College at Fort McNair in Washington, D.C., is the apex of the American system of military Professional Military Education (PME) Schools. The War College has trained such leading foreign policy specialists as former National Security Director Brent Scowcroft, former Secretary of State Colin Powell, and current National Security Director James Jones.